A natural history study of Chinese individuals with Duchenne muscular dystrophy: Results from 2 years of follow-up and beyond - Xihua Li; Xinying Yang; Xingzhi Chang; Zhiqiang Wang; Siqi Hong; Wenhua Zhu; Qi Shen; Yangmei Zhou; Shuiqing Zhu; Ying Xu Gao; Caiping Jia (PLoS ONE, 2026)
Background and Objectives Natural history studies in Duchenne muscular dystrophy (DMD) can help to elucidate the trajectory of the disease, understand the importance of clinical milestones, and identify endpoints for clinical trials. We present data from a natural history study of DMD in Chinese individuals with a follow-up of up to 30 months. Methods This was a multicenter, prospective, single-cohort study in Chinese boys of any age with a confirmed diagnosis of DMD. Participants were allocated into one of three groups: Group 1 (ambulatory, < 6 years old); Group 2 (ambulatory, ≥ 6 years old); and Group 3 (non-ambulatory, any age). Endpoints included time to life-altering clinical milestones, North Star Ambulatory Assessment (NSAA; Groups 1 and 2), Performance of Upper Limb 2.0 (PUL2.0; Groups 2 and 3), pulmonary function (Groups 2 and 3), left ventricular ejection fraction (LVEF; Groups 2 and 3), and quality of life endpoints. Results 312 participants were enrolled (Group 1, n = 99; Group 2, n = 177; Group 3, n = 36). Mean (SD) age at baseline in the total study population was 7.9 (3.4) years. Median (95% confidence interval) age at failure to walk in the total study population was 13.1 (12.5–14.1) years. Up to 30 months, NSAA total score deteriorated in Group 2 with no decline in Group 1. PUL 2.0 score declined in both Groups 2 and 3. Pulmonary function decreased in Groups 2 and 3 but to a greater extent in Group 3. Changes in LVEF were minimal. Quality of life deteriorated over time, particularly in Group 3. Discussion These data extend the 1-year findings from the same study and demonstrate the progression of DMD in Chinese individuals of differing age and ambulatory status. Registration information ClinicalTrials.gov identifier: NCT03760029.